Identification of essential oils with activity against stationary phase Staphylococcus aureus - Shuzhen Xiao; Peng Cui; Wanliang Shi; Ying Zhang (BMC, 2020)
Abstract Background Staphylococcus aureus is the most dominant human pathogen, responsible for a variety of chronic and severe infections. There is mounting evidence that persisters are associated with treatment failure and relapse of persistent infections. While some essential oils were reported to have antimicrobial activity against growing S. aureus, activity of essential oils against the stationary phase S. aureus enriched in persisters has not been investigated. Methods In this study, we evaluated the activity of 143 essential oils against both growing and stationary phase S. aureus by minimum inhibitory concentration (MIC) testing and by colony forming unit assay. Results We identified 39 essential oils (Oregano, Cinnamon bark, Thyme white, Bandit "Thieves", Lemongrass (Cymbopogon flexuosus), Sandalwood oil, Health shield, Allspice, Amyris, Palmarosa, Cinnamon leaf, Clove bud, Citronella, Geranium bourbon, Marjoram, Peppermint, Lemongrass, Cornmint, Elemi, Ho wood, Head ease, Lemon eucalyptus, Litsea cubeba, Myrrh, Parsley seed, Coriander oil, Dillweed, Hyssop, Neroli, Rosewood oil, Tea tree, Cajeput, Clove bud, Lavender, Sleep tight, Vetiver, Palo santo, Sage oil, Yarrow) at 0.5% (v/v) concentration, 10 essential oils (Cinnamon bark, Oregano, Thyme white, Bandit "Thieves", Lemongrass, Sandalwood oil, Health shield, Allspice, Amyris, Palmarosa at 0.25% (v/v) concentration, and 7 essential oils (Oregano, Cinnamon bark, Thyme white, Lemongrass, Allspice, Amyris, Palmarosa at 0.125% (v/v) concentration to have high activity against stationary phase S. aureus with no visible growth on agar plates after five-day exposure. Among the 10 essential oils which showed high activity at 0.25% (v/v) concentration, 9 (Oregano, Cinnamon bark, Thyme white, Bandit "Thieves", Lemongrass, Health shield, Allspice, Palmarosa, Amyris showed higher activity than the known persister drug tosufloxacin, while Sandalwood oil had activity at a higher concentration. In Oregano essential oil combination studies with antibiotics, Oregano plus tosufloxacin (or levofloxacin, ciprofloxacin) and rifampin completely eradicated stationary phase S. aureus cells, but had no apparent enhancement for linezolid, vancomycin, sulfamethoxazole, trimethoprim, azithromycin or gentamicin. Conclusions Our findings indicate that some essential oils have excellent activity against both growing and stationary phase S. aureus. Further studies are needed to identify the active components, evaluate safety, pharmacokinetics, and their activity to eradicate S. aureus infections in vivo.